A reproducible method for the isolation and expansion of ovine mesenchymal stromal cells from bone marrow for use in regenerative medicine preclinical studies. (18th November 2016) - Caminal, Marta; Vélez, Roberto; Rabanal, Rosa Maria; Vivas, Daniel; Batlle‐Morera, Laura; Aguirre, Màrius; Barquinero, Jordi; García, Joan; Vives, Joaquim
Abstract: The use of multipotent mesenchymal stromal cells (MSCs) as candidate medicines for treating a variety of pathologies is based on their qualities as either progenitors for the regeneration of damaged tissue or producers of a number of molecules with pharmacological properties. Preclinical product development programmes include the use of well characterized cell populations for proof of efficacy and safety studies before testing in humans. In the field of orthopaedics, an increasing number of translational studies use sheep as an in vivo test system because of the similarities with humans in size and musculoskeletal architecture. However, robust and reproducible methods for the isolation, expansion, manipulation and characterization of ovine MSCs have not yet been standardised. The present study describes a method for isolation and expansion of fibroblastic‐like, adherent ovine MSCs that express CD44, CD90, CD140a, CD105 and CD166, and display trilineage differentiation potential. The 3‐week bioprocess proposed here typically yielded cell densities of 1.4 × 10 4 MSCs/cm 2 at passage 2, with an expansion factor of 37.8 and approximately eight cumulative population doublings. The osteogenic potential of MSCs derived following this methodology was further evaluated in vivo in a translational model of osteonecrosis of the femoral head, in which the persistence of grafted cells in the host tissue and their lineage commitment into osteoblasts and osteocytes was demonstrated by tracking enhanced green fluorescent protein‐labelled cells. Copyright © 2016 John Wiley & Sons, Ltd.